Metode Word Square Dipadukan Ajaran Tri Kaya Parisudha Untuk Meningkatkan Aktivitas dan Prestasi Belajar Pendidikan Agama Hindu dan Budi Pekerti - Sriasih, Ni Wayan; Mastiningsih, Ni Nyoman (STKIP AGAMA HINDU SINGARAJA, 2024)
This research aims to improve learning activities and achievement in Hindu religious education and character in class VIII C students of SMP Negeri 2 Sawan, Sawan District, Buleleng Regency through the application of the Word Square Method combined with the Tri Kaya Parisudha Learning Model. This research is classroom action research carried out in two cycles consisting of planning, action implementation, observation, evaluation, analysis and reflection stages carried out in each cycle. The subjects of this research were students in class VIII C of SMP Negeri 2 Sawan, in the even semester, totaling 32 students consisting of 15 men and 17 women. Student activity data is collected using the observation method, while student learning achievement data is collected using the testing method in the form of objective tests in the form of multiple choices. The results of this research show that there was an increase in the Learning Activities of class VIII C SMP Negeri 2 Sawan in the Hindu Religion subject in cycle I with a score of 60%, while in cycle II with a score of 79%. So there is an increase in student activity in the learning process by 19%. For Student Learning Achievement, in the first cycle the class average score was 71.25 with an Absorption Capacity of 71.25% and Learning Completeness 62.5%. Meanwhile, in cycle II the class average was 80.62 with Absorption Capacity 80.62% and Learning Completeness 81.25%. Based on the results of this research, it means that there has been an increase in student activity and learning achievement in class VIII C of SMP Negeri 2 Sawan, Sawan District, Buleleng Regency. It is hoped that the Word Square method combined with the Tri Kaya Parisudha learning model can be used in the teaching and learning process to improve student activity and learning achievement in Hinduism subjects and other subjects.